Teaching skills, an innovation in virtual learning Environments in higher education - Carlos Arturo Vega Lebrún; Mariano Sánchez Cuevas; Genoveva Rosano Ortega; Silvia Elena Amador Pérez (Universidad de Guadalajara, 2021)
The emergency closure of educational institutions, in the face of the health contingency due to Covid-19, has prompted the rethinking of the models of teaching competencies to adapt to virtual learning environments (VLE). The objective of this study is to design and validate a model of teaching competencies in VLE, with the support of virtual laboratories, to ensure the quality of higher education during the covid-19 pandemic. A quantitative and correlational methodology was used in a case study. The research is divided into two methodological moments: the design of the model and its validation. The instruments used were a comparative analysis matrix and a Likert-type scale. 5 650 students and 41 teachers participated in the validation cap. The results highlight the need for teacher development, mainly in digital and research skills. One weakness of the study is the lack of weighting of the quality indicators. The proposed model represents an innovation in the definition of indicators, in the form of competencies, for the assurance of educational quality in VLE. It is concluded that the proposed model is pertinent for the assurance of educational quality in VLE.